Engineering of Bioenergy Crops: Dominant Genetic Approaches to Improve Polysaccharide Properties and Composition in Biomass - Brandon, Andrew G.; Scheller, Henrik V. (Frontiers in Plant Science, 2020)
Large-scale, sustainable production of lignocellulosic bioenergy from biomass will depend on a variety of dedicated bioenergy crops. Despite their great genetic diversity, prospective bioenergy crops share many similarities in the polysaccharide composition of their cell walls, and the changes needed to optimize them for conversion are largely universal. Therefore, biomass modification strategies that do not depend on genetic background or require mutant varieties are extremely valuable. Due to their preferential fermentation and conversion by microorganisms downstream, the ideal bioenergy crop should contain a high proportion of C6-sugars in polysaccharides like cellulose, callose, galactan and mixed-linkage glucans. In addition, the biomass should be reduced in inhibitors of fermentation like pentoses and acetate. Finally, the overall complexity of the plant cell wall should be modified to reduce its recalcitrance to enzymatic deconstruction in ways that do no compromise plant health or come at a yield penalty. This review will focus on progress in the use of a variety of genetically dominant strategies to reach these ideals. Due to the breadth and volume of research in the field of lignin bioengineering, this review will instead focus on approaches to improve polysaccharide component plant biomass. Carbohydrate content can be dramatically increased by transgenic overexpression of enzymes involved in cell wall polysaccharide biosynthesis. Additionally, the recalcitrance of the cell wall can be reduced via the overexpression of native or non-native carbohydrate active enzymes like glycosyl hydrolases or carbohydrate esterases. Some research in this area has focused on engineering plants that accumulate cell wall-degrading enzymes that are sequestered to organelles or only active at very high temperatures. The rationale being that, in order to avoid potential negative effects of cell wall modification during plant growth, the enzymes could be activated post-harvest and post-maturation of the cell wall. A potentially significant limitation of this approach is that at harvest, the cell wall is heavily lignified, making the substrates for these enzymes inaccessible and their activity ineffective. Therefore, this review will only include research employing enzymes that are at least partially active under the ambient conditions of plant growth and cell wall development.